Teen Safety in Cyberspace - Kate Fogarty (EDIS)
If you believe e-mail, blogs, text messaging, instant messaging, social networking sites, and 3-D virtual worlds (with avatars) are a completely harmless way for teens to communicate, think again! This revised 5-page fact sheet defines online sexual solicitation and cyberbullying, explains the risk factors and negative effects of these communications, and outlines effective ways to protect youth from harm. Written by Kate Fogarty and published by the UF Department of Family Youth and Community Sciences, March 2011.